Design and Dynamic Analysis of the Multi-link Mechanism for Variable Compression Ratio Engine - Xu Kai; Feng Zengming; Yang Jinxing; Chu Yaxu (Jixie chuandong)
The compression ratio of engines is one of the factors affecting the thermal efficiency of gasoline engines. The engine needs to match the best compression ratio according to the actual conditions to meet the actual requirements. Therefore, variable compression ratio technology can help achieve a balance between engine power and fuel economy under different operating conditions. Thus, a multi-link mechanism for variable compression ratio engine is designed based on the engine principle. The correctness of the mechanism design is verified by kinematics theory modeling calculation and comparative analysis of simulation results. Based on multi-body dynamics theory and considering boundary conditions such as combustion load and crankshaft speed comprehensively, the variation rule of the multi-link mechanism with control shaft rotation angle is explored; the kinematic and dynamic characteristics of the multi-link mechanism under different compression ratio conditions are evaluated, compared and analyzed in detail with those of the traditional single-link mechanism. The results show that the multi-link mechanism can realize real-time variable compression ratio to meet the actual operating conditions, has mechanical advantages in power amplification characteristics and restraining friction between piston and cylinder wall, and brings additional dynamic benefits in engine vibration.